2020
DOI: 10.1038/s41598-020-68158-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunization against leukemia inhibitory factor and its receptor suppresses tumor formation of breast cancer initiating cells in BALB/c mouse

Abstract: Immunotherapy is a promising approach for specific targeting of cancer cells. Leukemia inhibitory factor (Lif) regulates several features of cancers and cancer stem cells (cScs) through binding to Lif receptor (LIFR). In this study, we investigated the consensus of LIF and LIFR immunization on the growth of mouse mammary tumors. For this purpose, mouse LIF and LIFR were designed as truncated proteins, expressed in E. coli and then injected to mice as individual and mixed antigens. The results showed the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…24 Interestingly, LIF neutralization was associated with strong inhibition of tumor growth in several preclinical models. 25,26 A recent study has also shown that LIF blockade is associated with an increased production of CXCL9 by macrophages and a concomitant decrease in CD206, CD163 and CCL2. 26 In our study, while baseline plasma LIF was associated with an intratumoral expression of LIF, no correlation was found for either CCL2, CD206 or CXCL9 (Supplementary Figure S6 We therefore assessed whether the peripheral level of LIF was associated with specific tumor microenvironment features.…”
Section: Discussionmentioning
confidence: 96%
“…24 Interestingly, LIF neutralization was associated with strong inhibition of tumor growth in several preclinical models. 25,26 A recent study has also shown that LIF blockade is associated with an increased production of CXCL9 by macrophages and a concomitant decrease in CD206, CD163 and CCL2. 26 In our study, while baseline plasma LIF was associated with an intratumoral expression of LIF, no correlation was found for either CCL2, CD206 or CXCL9 (Supplementary Figure S6 We therefore assessed whether the peripheral level of LIF was associated with specific tumor microenvironment features.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the expression of LIF in the stroma was significantly elevated in breast cancer tissue sections from lean patients. Interestingly, the high expression of LIF has been connected to increased tumor progression, stemness, therapy resistance and TME modulation in various cancer entities in multiple in vitro and in vivo models [ 98 ] and the immunization against LIF or LIFR suppressed the tumor formation, growth and metastasis in a mammary xenograft mouse model [ 99 ]. Our findings clearly suggest that obesity influences the TME.…”
Section: Discussionmentioning
confidence: 99%
“…This promotion occurs through the activation of AKT, which activates the downstream mTOR signaling pathway ( 24 ). At the same time, LIF was reversed to promote tumor formation and metastasis ( 25 ). However, the role of LIF in ccRCC has not been studied.…”
Section: Discussionmentioning
confidence: 99%